Inovasi Produksi MP-ASI Lokal Berbasis Komunitas di Desa Blang Teue Kota Lhokseumawe - Ardilla, Arista; Zulkarnaini, Zulkarnaini; Sutrisna, Eka; Aulia, M. Kahfi; Maulida, Husna; Yasmine, Dian; Maula, Zaqiul; Irawan, Silvia; Azwani, M. Faza Raka (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2025)
Background: Stunting remains one of the leading public health problems in Indonesia, including in Blang Teue Village, Lhokseumawe City, where the prevalence reaches 27.6%. Purpose: This community service program aimed to develop an innovative community-based production model for locally sourced complementary feeding (MP-ASI) through the empowerment of PKK women’s groups and Posyandu cadres. The program focused on improving nutritional knowledge, production skills, and digital capabilities related to child growth monitoring. Methods: The Participatory Action Research (PAR) approach was employed through several stages, including identification of local food resources, training on the production of nutrient-dense complementary foods made from mackerel and moringa leaves, and digital education for promotion and child growth recording using Google Sheets. Results: The program demonstrated significant improvements, including an increase in knowledge related to stunting prevention (participants in the “good” category rose from 5% to 72.5%), enhanced production skills for NABUNG complementary food (85%), and improved digital literacy among Posyandu cadres in creating educational media and recording child growth data. Conclusion: This program successfully developed an innovative community-based MP-ASI production model that not only supports stunting prevention but also strengthens digital literacy and fosters community independence in managing child nutrition